Phân tích đa thức sau thành nhân tử. 2x(x-1)-3x+3

Question

Phân tích đa thức sau thành nhân tử. 2x(x-1)-3x+3

in progress 0
Adalyn 9 giờ 2021-09-16T17:50:35+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-16T17:51:36+00:00

    Đáp án:

    2x(x – 1) – 3x + 3 = 2x( x -1) – 3(x – 1) = (2x – 3)( x -1)

    0
    2021-09-16T17:52:08+00:00

    Đáp án:

    Giải thích các bước giải:

    2x(x-1)-3x+3

    =2x(x-1)-(3x-3)

    =2x(x-1)-3(x-1)

    =(2x-3)(x-1)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )